Automatic Voltage Regulator as a Voltage Control in 1 Phase Axial Generator System - Apriani, Yosi; Saleh, Zulkiffli; Suppermen, Suppermen; Sofian, Ian Mochamad (Universitas Muhammadiyah Yogyakarta, 2021)
A constant output voltage on a generator is very important to produce the expected power supply. Changes in the output voltage of a generator are influenced by various disturbing factors, one of which is load and Rotations Per Minute (RPM) which are not always constant. Therefore we need a special regulator equipment to keep the generator output voltage constant. The problem of voltage instability during load changes must be overcome to keep the voltage constant, so that equipment is needed that can control the voltage stability. This tool is the Automatic Voltage Regulator (AVR). The purpose of this study is to design a voltage control device in a single phase axial generator system. The research method used consists of 3 stages, namely: 1). Design and design of tools, 2). Stages of making tools, 3). Stages of testing the tool. The results of the research were obtained when an axial generator with an inner air gap of 0.4 cm, outer 0.5 cm and rpm 2589. The output voltage of the generator began to decrease significantly until it reached -70 volts and rpm also decreased to -200. In contrast, when the generator is operated using the AVR, the reduction only reaches -30 volts. However, when the generator is operated with AVR, the decrease in rpm is greater until it reaches -220.